Pioglitazone Reduces β Amyloid Levels via Inhibition of PPARγ Phosphorylation in a Neuronal Model of Alzheimer’s Disease - Quan, Qiankun; Qian, Yihua; Li, Xi; Li, Ming (Frontiers in Aging Neuroscience, 2019)
It has been demonstrated that peroxisome proliferator-activated receptor γ (PPARγ) can regulate the transcription of its target gene, insulin-degrading enzyme (IDE) , and thus enhance the expression of the IDE protein. The protein can degrade β amyloid (Aβ), a core pathological product of Alzheimer’s disease (AD). PPARγ can also regulate the transcription of other target gene, β-amyloid cleavage enzyme 1 (BACE1), and thus inhibit the expression of the BACE1 protein. BACE1 can hydrolyze amyloid precursor protein (APP), the precursor of Aβ. In adipose tissue, PPARγ agonists can inhibit the phosphorylation of PPARγ by inhibiting cyclin-dependent kinase 5 (CDK5), which in turn affects the expression of target genes regulated by PPARγ. PPARγ agonists may also exert inhibitory effects on the phosphorylation of PPARγ in the brain, thereby affecting the expression of the aforementioned PPARγ target genes and reducing Aβ levels. The present study confirmed this hypothesis by showing that PPARγ agonist pioglitazone attenuated the neuronal apoptosis of primary rat hippocampal neurons induced by Aβ1-42, downregulated CDK5 expression, weakened the binding of CDK5 to PPARγ, reduced PPARγ phosphorylation, increased the expression of PPARγ and IDE, decreased the expression of BACE1, reduced APP production, and downregulated intraneuronal Aβ1-42 levels. These effects were inhibited by the PPARγ antagonist GW9662. After CDK5 silencing with CDK5 shRNA, the above effect of pioglitazone was not observed, except when upregulating the expression of PPARγ in Aβ1-42 treated neurons. In conclusion, this study demonstrated that pioglitazone could inhibit the phosphorylation of PPARγ in vitro by inhibiting CDK5 expression, which in turn affected the expression of PPARγ target genes Ide and Bace1, thereby promoting Aβ degradation and reducing Aβ production. This reduced Aβ levels in the brain, thereby exerting neuroprotective effects in an AD model.